Inventory of macrofungi at peat swamp forest area, Kapuas Hulu, West Kalimantan - Noverita Noverita; Tatang Mitra Setia (Journal of Microbial Systematics and Biotechnology, 2019)
The areas surrounding peat swamp forest at Dusun Meliau and Bukit Peninjau, Kapuas Hulu, West Kalimantan host a diverse species of flora and fauna, including macrofungi. However, the information on the macrofungal diversity in this area has not been reported. The goal of this study was to obtain information on the diversity of macrofungi that can be used as food and medicine. Data was collected by direct modified collection method using plot (10 × 20 m) with interval 10 m along the transect line. A total of 79 specimens of macrofungi discovered from the two locations, of which 23 and 66 specimens were collected from Dusun Meliau and Bukit Peninjau, respectively. Of the 79 macrofungi specimens, 16 specimens were potential as a food source, and 41 as medicine. The macrofungi in this study was dominated by members of Ordo Aphyllophorales.